Policies for Inclusive Urbanisation in China - Koen, Vincent (OECD Economics Department Working Papers, 2013)
Urbanisation in China has long been held back by various restrictions on land and internal migration but has taken off since the 1990s, as these impediments started to be gradually relaxed. People have moved in large numbers to richer cities, where productivity is higher and has increased further thanks to agglomeration effects. In the process, the rural-urban income differential has narrowed. Urbanisation also entails costs, however, notably in the form of congestion, all the more so as public transport provision has not kept up. Demand for living space is set to continue to increase as living standards improve, putting pressure on land prices. This can be offset by relaxing the very stringent restrictions on the use of agricultural land for building. For migrants to better integrate in the cities where they work, their access and that of their families to education, health and other social services must continue to improve, in particular via further changes to the registration system, coupled with more market-based rules on land ownership and use